2018
DOI: 10.1371/journal.pone.0190078
|View full text |Cite
|
Sign up to set email alerts
|

Colon dysregulation in methamphetamine self-administering HIV-1 transgenic rats

Abstract: The integrity and function of the gut is impaired in HIV-infected individuals, and gut pathogenesis may play a role in several HIV-associated disorders. Methamphetamine is a popular illicit drug abused by HIV-infected individuals. However, the effect of methamphetamine on the gut and its potential to exacerbate HIV-associated gut pathology is not known. To shed light on this scenario, we evaluated colon barrier pathology in a rat model of the human comorbid condition. Intestinal barrier integrity and permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…First, at least Meth can alter GI function in humans by causing intestinal ischemia [73] and infarction [74], and it can also lead to reductions in GI motility and paralytic ileus [75]. In animals, self-administration of Meth increases colon permeability [76] and gut toxicity [77]. Second, psychostimulants have long been used to suppress appetite as an aid to weight loss [78] and it is known that individuals with eating disorders have worsened symptoms and poorer outcomes if they co-abuse stimulants such as Meth [79].…”
Section: Discussionmentioning
confidence: 99%
“…First, at least Meth can alter GI function in humans by causing intestinal ischemia [73] and infarction [74], and it can also lead to reductions in GI motility and paralytic ileus [75]. In animals, self-administration of Meth increases colon permeability [76] and gut toxicity [77]. Second, psychostimulants have long been used to suppress appetite as an aid to weight loss [78] and it is known that individuals with eating disorders have worsened symptoms and poorer outcomes if they co-abuse stimulants such as Meth [79].…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine can destroy the blood-brain barrier, leading to increased blood-brain barrier permeability and to a reduced expression of tight junction protein, which then induces neuroinflammation ( Martins et al, 2011 ; Northrop and Yamamoto, 2015 ; Turowski and Kenny, 2015 ). Furthermore, this drug can also reduce the level of ZO-1 protein in the rat colon and change colon permeability ( Persons et al, 2018 ). In this study, compared with the C group, the expression levels of occludin a and occludin b mRNAs in the zebrafish brain and intestine were significantly reduced in the M group.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, Figures 3 and 4 illustrate that METH changes expression for a number of genes involved in directing arachidonic acid metabolism toward PGE2 production that could be dependent on LPS derived from a leaky gut. In fact, Persons et al [56] showed that METH self-administration in Fischer 344 rats resulted in lower expression of gut tight junction proteins claudin-1 and ZO-1 as well as a morphological disorganization of these proteins in the colon. Additionally, human METH users suffer from bowel ischemia which is associated with loss of gut integrity [57,58] that may lead to the entry of LPS into the brain parenchyma as shown in rats following a METH-induced compromise of the blood-brain-barrier [59].…”
Section: Discussionmentioning
confidence: 99%